Exploratory study of graduate-level instructor’s perception of teaching critical thinking - Van Der Werff, Jay A. (Kansas State University, 2016)
Higher learning institutions identify the teaching of critical thinking skills to students as a goal of the academic programs offered. This study examined faculty perceptions for teaching critical thinking skills at the U.S. Army’s Command and General Staff College (CGSC). CGSC is charged with educating the nation’s mid-career military officers for the world’s complexities that will challenge them during the next 5 to 10 years of their career. To accomplish this task, CGSC has a dedicated faculty development program to expose new faculty to critical thinking concepts and principles, and a curriculum that integrates critical thinking throughout the lesson plans designed to improve the students’ critical thinking skills during the course of the academic year. An exploratory mixed methods approach was used to examine the research questions. Faculty participated in a survey providing quantitative results (n = 83), and eight volunteers were interviewed expanding upon the quantitative results. Analysis of the quantitative results showed that instructors believe the most effective teaching techniques for fostering critical thinking skills are small group facilitated discussion, role play/simulation – which is manifested in planning exercises – and the use of case studies. Instructors identified monitoring classroom discussions and providing feedback on argumentative essays as the most effective techniques for assessing critical thinking. Analysis of the qualitative results uncovered three themes for effective teaching of critical thinking skills–use of instructional strategies, effectiveness in teaching, and faculty development–and four areas viewed as inhibitors to fostering critical thinking skills among students–faculty development, doctrine as a constraint, student experience, and time restraints in the curriculum. Those interviewed believed the institution has an effective program for fostering critical thinking skills among students, but identified areas for improvement in the faculty development program and the curriculum. Instructors considered the faculty development program at CGSC an effective program that provides a foundation for teaching critical thinking skills, and offered recommendations to improve the existing program. The study showed that faculty perceptions for fostering critical thinking skills among students are positive, with a belief that critical thinking skills may be taught at the graduate level.
Keywords: Critical thinking; Faculty; Graduate education